Nicopolis Ad Istrum. A Roman to Early Byzantine City. The Pottery and Glass - Poulter, Andrew G. (Reports of the Research Committee of the Society of Antiquaries of London, 1999)
This is the first volume describing archaeological excavations undertaken from 1985 at Nicopolis ad Istrum, a Roman and Early Byzantine town in northern Bulgaria. This volume provides a catalogue of the glass and pottery recovered, describing the diagnostic types and typological sequence. Some observations about production and the economic and social implications of the pottery and glass are also made.